Overexpression of soluble recombinant Thermus thermophilus (Tth) DNA polymerase in Escherichia coli BL21(DE3) using an MBP fusion tag as a solubility enhancer - Iman Permana Maksum, Diandra Firdiani Utami, Eva Annisa Nurhakim, Yosua, Sriwidodo, Muhammad Yusuf, Muhammad Fadhlillah, Ryan Adibagus Haryanto (Journal of Applied Pharmaceutical Science, 2022)
Tth DNA polymerase is a thermostable enzyme derived from Thermus thermophilus and acts as a DNA polymerase and reverse transcriptase. Escherichia coli is used for large-scale enzyme production because of its cost-effectiveness, rapid growth, and increased recombinant protein expression, but inclusion bodies can be formed during intracellular protein expression, so the maltose-binding protein (MBP) tag was used to improve the expression of soluble protein. The Tth DNA polymerase gene was optimized to have a codon adaptive index of 1.00% and 60.64% Guanine and Cytosine (GC) content, then inserted into E. coli BL21(DE3), which harbors pD861-His-Tth DNA polymerase and pD861-MBP-Tth DNA polymerase. The induction and postinduction incubation time were optimized to express pD861-His-Tth DNA polymerase and pD861-MBP-Tth DNA polymerase in the soluble form. The total protein concentration of His-Tth DNA polymerase is 3.9095 mg/ml while for MBP-Tth DNA polymerase it is 33.541 mg/ml; protein levels after optimization based on densitometry analysis show MBP-Tth DNA polymerase is seven times higher than His-Tth DNA polymerase. This indicates that MBP tag fusion increases the amount of soluble protein produced.
Keywords: Escherichia coli BL21(DE3), pD861-His, pD861-MBP, RTPCR, Tth DNA polymerase